PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 11 DOMPAS KECAMATAN BUKIT BATU - Fitri Sardi; Lazim N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The research aims to improve the student’s learning result of social studies by applying cooperatif learning model make a match.The problem of this research is the weakness of student’s learning result of social studies from the fourth grade students of SD Negeri 11 Dompas,there are 20 students. The KKM of this school is 66, only 8 students (40.00%) were above the KKM, while 12 students (60.00%) are under the KKM, with the average value of the class is 64.70. This research is a classroom action research (CAR) by applying cooperative learning model make a match.At the first meeting, the activities of teachers percentage 54.16% enough category, then a second meeting increased to 70.83% both categories. Then at the first meeting of the second cycle increased to 83.33% category very good.the second meeting up again with a percentage of 91.66%. increased student activity each meeting. At the first meeting of the first cycle of student activity percentage is 41.66% enough category, then the second meeting of the second cycle increased to 66.66% both categories. At the first meeting of the second cycle increased to 83.33% very good category. At the second meeting increased again the percentage is 87.50% (very good). The average value of the basic score before implementation of cooperative learning make a match is 64.70. in the UHI learning result was 74.50 and then on the second cycle increased again which can be seen in UHII replay value with an average value of students was 79.50.  Keywords: cooperative model make a match, learning result of social studies